The impact of plant extracts on genotoxicity induced by tobacco products - MAJI JOSE; VENGAL IPE VARGHESE; VARSHA JAYAKAR; VINAYAK LOKAPUR; SRINIVASA K.; ALI MOHAMMED ABDULLAH BAWAZIR; MANJULA SHANTARAM (International Journal of Pharma and Bio Sciences, 2019)
Tobacco is a menace that has taken over millions of people all over the world, cutting through the nation and social barriers. It is highly alarming that tobacco products which were usually consumed by a small section of the population today are part of the modern urban and rural lifestyle and even children of school going age are getting into these habits. It is well known that tobacco contains chemical constituents which are carcinogenic and cause various mucosal lesions ranging from chewers mucosa to potentially malignant lesions which may progress to oral cancer. In India, people consume tobacco in different forms. Geno-toxicity is a word in genetics well-defined as a destructive effect on a cell’s genetic material affecting its integrity. Numerous studies have been conducted to identify the DNA damage in cells exposed to smokeless tobacco and related compounds. All three samples of tobacco which included unprocessed tobacco, tobacco processed for chewing and commercially dispensed tobacco in sachets induce oxidative stress and cytotoxic cell death. It was further evaluated for the oxidative DNA damage using two popular geno-toxicity assays i.e. comet assay and micronucleus assay. Comet assay is a sensitive technique for the detection of DNA damage at the level of an individual eukaryotic cell. Micronuclei are extra nuclear bodies of chromatin material formed as a consequence of chromosome breakage or aneuploidy. There are ample evidences from invitro and invivo studies which prove that tobacco induces DNA strand breaks, forms DNA adducts and causes mutagenic and cytogenetic effects. The present study has confirmed that tobacco induces genotoxic effect and this effect can be partly abridged by mango leaf, coconut husk and areca husk extract.